Importancia del manejo agricola para la biodiversidad: caso de las hormigas en caña de azucar - Ramirez R, M:=700 1 Armbrecht P, I.; Enriquez L, L.
(ES, En)
Ilus., 38 ref.
Keywords: FORMICIDAE; BIODIVERSIDAD; INSECTA; AGRICULTURA ORGANICA; SACCHARUM OFFICINARUM; COLOMBIA; HORMIGAS